Motivasi Intrinsik dalam Perspektif Muhammad Anwar Al-SyarQawi - Ba'ina, Sitti; Muhlis, Achmad (LPPAIK Universitas Muhammadiyah Bandung, 2025)
This study aims to analyze the nature, advantages, and weaknesses of intrinsic motivation based on the views of Anwar Muhammad Al-Syarqawi. The learning process in the classroom is often still stuck in the routine of delivering material without providing enough space for students to find intrinsic motivation, so that students tend to understand learning as limited to memorization, while aspects of attitude change and personality formation are not paid much attention. This study uses a qualitative approach of library research with the main source of the book Al-Ta'allum Al-Nadhariyat wa Al-Tatbiqiyyah by Al-Syarkawi. The results of the study show that intrinsic motivation according to Al-Syarkawi is rooted in the spiritual and cognitive drive of individuals, which has great potential in shaping meaningful learning, but requires the support of educators in its application. Intrinsic motivation from the Syarkawi perspective has several advantages, namely it can trigger the spirit of learning naturally and sustainably, has a strong spiritual and cognitive foundation, tends to produce more meaningful learning and lasting behavioral changes. Apart from the advantages there are also disadvantages, namely it is highly dependent on the internal conditions of the individual, difficult to measure or imposed externally by the educator or the learning environment, requires educators who are not only able to provide stimulation, and the last is less effective for students who are not fully able to connect learning with spiritual values or deeper life goals.